PENGARUH PELATIHAN KERJA, MOTIVASI KERJA, DISIPLIN KERJA PADA PERUSAHAAN UMUM DAERAH PASAR JOYOBOYO KOTA KEDIRI - Putri Mega Ayu Suciati; Heru Sutapa; Nizar Zakaria (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Employee performance in regional public enterprises is determined not only by technical competence but also by the interaction of work training, work motivation, and work discipline. This study aims to analyze the effect of work training, work motivation, and work discipline on employee performance at Perusahaan Umum Daerah (Perumda) Pasar Joyoboyo, Kediri City. The study used an explanatory quantitative approach with a saturated sampling technique involving all 41 employees as respondents. Data were collected through a 1-4 Likert scale questionnaire, observation, and literature review, and analyzed using multiple linear regression with IBM SPSS after passing validity, reliability, and classical assumption test (normality, linearity, multicollinearity, and heteroscedasticity). The result show that work training has a positive and significant effect on employee performance (t = 2.774; sig. 0.009), work motivation has a significant but negative effect (t = -3.379; sig. 0.002), while work discipline has the most dominant positive and significant effect (t = 3.985; sig. 0.000). Simultaneously, the three variables significatly affect employee performance (F = 14.444; sig. 0.000), contributing 53,9% (R2 = 0.539) to the variation in employee performance. These findings confirm that work discipline is the primary determinant of employee performance at Perumda Pasar Joyoboyo, while training provides a proven positive contribution, and motivation requires further evaluation to optimize its contribution to performance improvement.